"الفساد في ضوء القرآن الكريم" أنواعه، أسبابه، علاجه - بكاري, عبد المالك; شليق, إسماعيل; بلغيث, أسامة (جامعة الوادي-university of eloued, 2014)
This study is an application sample to the theory of al-tafseer al mawdou’i (objective interpretation). It deals with the various etymological forms of fasaad (corruption) mentioned in many Quranic Macci and Madani verses. Specifically, the study focuses on the present, past and past participle forms of fasaad with some concentration on the quality meanings, opinions and benefits subtracted from these forms. In addition, the study attempts to induce the various causes of this fasaad as revealed by the Quranic verses in order to show the distinctive feature of Quran in serving humans and solving their problems. The main rational behind dealing with such a topic is to change this life of Omma that is full of fasaad of both the individual and the group in order to save it from the allurements of life and the torture of the life after.